Clinical impact of herpesvirus entry mediator expression in human hepatocellular carcinoma. Issue 2 (January 2015) - Hokuto, Daisuke; Sho, Masayuki; Yamato, Ichiro; Yasuda, Satoshi; Obara, Shinsaku; Nomi, Takeo; Nakajima, Yoshiyuki
Abstract Background Herpes virus entry mediator (HVEM), also known as tumour necrosis factor receptor (TNFR) superfamily 14, regulates a variety of physiological and pathological responses in both innate and acquired immunity. Although HVEM is also suggested to be a critical regulator in tumours, actual roles in human cancer are largely unknown. This study aimed to clarify clinical importance of HVEM in human hepatocellular carcinoma (HCC). Patients and methods We studied HVEM expression in 150 HCC patients to explore its clinical relevance, and we examined tumour infiltrating T cells and local immune status of them. Results HVEM was expressed in HCC cells, while no or only limited expression was observed in normal tissues in the liver. Tumour HVEM expression was significantly correlated with age, serum protein induced by vitamin K absence or antagonist-II (PIVKA-II) level, vascular invasion and tumour node metastasis (TNM) stage. Furthermore, tumour HVEM expression significantly correlated with postoperative recurrence and survival. Importantly, multivariate analysis indicated that the HVEM status had an independent prognostic value. Furthermore, HVEM status was inversely correlated with tumour-infiltrating CD4+, CD8+ and CD45RO+ lymphocytes. In addition, it was also associated with reduced expression of perforin, granzyme B and interferon-γ (IFN-γ). Taken together, tumour-expressing HVEM plays a functionally important role in HCC. Conclusion Tumour-expressing HVEM plays a critical role in human HCC, possibly through regulating immune evasion. Therefore, targeting HVEM may be a novel promising therapeutic strategy for HCC.